O papel da proteína de fusão do vírus sincicial respiratório sobre a geração de redes extracelulares de neutrófilos (NETS) - Funchal, Giselle Afonso (2014)
Acute viral bronchiolitis is the most common respiratory illness in children in the first years of life and at least half of patients are diagnosed with respiratory tract infection by viruses such as Respiratory Syncytial Virus (RSV). Because RSV is extremely common disease it generates large number of hospitalizations and large costs to health systems. The RSV Fusion (F) Protein is essential for the infective cycle of the virus. Neutrophils and their products are present in the airways of RSV-infected patients who developed increased lung disease due to viral infection. Neutrophil Extracellular Traps (NETs) are formed by the release of the inner content of neutrophils (proteins from granules and DNA) in the extracellular space in response to different stimuli. They are essential to prevent the spread of microorganisms, which are killed by antimicrobial proteins that are anchored in networks of DNA, such as elastase and myeloperoxidase. The objective of this work is to characterize the effect of the RSV F protein on the generation of NETs. The F protein was capable of inducing the formation of NETs in vitro in a dose-dependent way with co-expression of neutrophil elastase and myeloperoxidase. The production of NETs in response to F protein was mediated by the TLR-4-receptor and was dependent on ROS production, p38 and ERK MAPK. Together, these data provide evidence that support the activation of specific signaling pathways by the F protein to induce the production of NETs. Excessive production of NETs can aggravate the inflammatory symptoms induced by infection with RSV.